Blockchain-based Decentralized Application for Electronic Voting using an Electronic ID - Monteiro, José Diogo Soares Albergaria Serejo (2020)
An electronic voting system that fully mimics real-world systems has long been desired. Until recently, it had not been possible to fully address the mandatory properties of a real-world voting scheme, simultaneously. Recently, with the onset of new technologies and research, however, it is not only possible to fulfill these very properties, but also to improve the anonymity and convenience of voting. A decentralized and self-tallying electronic voting protocol that substantially enhances the privacy of voters and diminishes centralization is developed in this work and presented in this dissertation. These properties are accomplished through a symbiotic relationship between the Ethereum Blockchain and the Portuguese electronic ID. Unlike previously proposed Blockchain e-voting protocols, this is the first implementation that more closely fulfills most of the security requirements of a real-world voting scheme. Furthermore, this system improves currently in-use e-Voting systems by using a self-tallying protocol. Thus, each voting citizen is able to compute the tally of the election and has complete control over their own vote. The execution of this protocol is enforced using the consensus mechanism that safeguards the Ethereum Blockchain. To prove its feasibility, its implementation was tested on the official Proof of Work (PoW) test network of Ethereum (known as Ropsten). The financial and computational breakdowns are on par with the leading Blockchain e-voting protocol.